2018
DOI: 10.5194/bg-15-6731-2018
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural controls on the decomposition dynamics of boreal upland forest moss tissues

Abstract: Mosses contribute an average of 20 % of boreal upland forest net primary productivity and are frequently observed to degrade slowly compared to vascular plants. If this is caused primarily by the chemical complexity of their tissues, moss decomposition could exhibit high temperature sensitivity (measured as Q 10 ) due to high activation energy, which would imply that soil organic carbon (SOC) stocks derived from moss remains are especially vulnerable to decomposition with warming. Alternatively, the physical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Notably, this study showed that the average SOC and soil TN contents of mosses in the shrub habitat were 133.35 g/kg and 9.99 g/kg, respectively; these values were significantly higher than the SOC and soil TN in the vegetated areas of the Maolan karst forest (54.72 g/kg and 4.67 g/kg) [33] and karst rocky desertification-affected secondary forests (80.40 g/kg and 2.80 g/kg) [32]. Mosses have a slower decomposition rate than vascular plants, resulting in high organic matter content in moss substrates [34]. Moreover, mosses can form symbiotic relationships with blue algae [35].…”
Section: Soil C N and P Contents And Stoichiometric Characteristics Of Different Restoration Stages Of Karst Rocky Desertification Areasmentioning
confidence: 99%
“…Notably, this study showed that the average SOC and soil TN contents of mosses in the shrub habitat were 133.35 g/kg and 9.99 g/kg, respectively; these values were significantly higher than the SOC and soil TN in the vegetated areas of the Maolan karst forest (54.72 g/kg and 4.67 g/kg) [33] and karst rocky desertification-affected secondary forests (80.40 g/kg and 2.80 g/kg) [32]. Mosses have a slower decomposition rate than vascular plants, resulting in high organic matter content in moss substrates [34]. Moreover, mosses can form symbiotic relationships with blue algae [35].…”
Section: Soil C N and P Contents And Stoichiometric Characteristics Of Different Restoration Stages Of Karst Rocky Desertification Areasmentioning
confidence: 99%
“…For instance, water retaining and insulating mosses control soil microclimate and microclimate-dependent nitrogen (N) mineralization (Gornall et al 2007;Bernier et al 2011;Elumeeva et al 2011;Soudzilovskaia et al 2013). Mosses also trap N directly from deposition, support biological N fixation and N uptake from soil (DeLuca et al 2002;Rousk et al 2013), and supply soil with litter of varying decomposability that may all influence soil N availability, organic matter pools, and, ultimately, vascular vegetation N availability (van der Wal et al 2001;Bengtsson et al 2018;Chiapusio et al 2018;Philben et al 2018). Additionally, moss effects on ecosystem functions may also vary due to environmental conditions such as changes in air temperature and precipitation (De Long et al 2016a;Lett et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moss N may for instance be lost via denitrification or via leeching to deeper soil layers (Johnson et al, 2007). Moss N has also been found to be more rapidly lost from moss litter than C during decomposition (Philben et al, 2018). Nevertheless, as moss mat coverage and shoot length increased with succession, moss TN per square meter will increase.…”
Section: Discussionmentioning
confidence: 99%